2021
DOI: 10.1186/s12957-021-02168-8
|View full text |Cite
|
Sign up to set email alerts
|

Immune infiltrating cells in cholangiocarcinoma may become clinical diagnostic markers: based on bioinformatics analysis

Abstract: Background Intrahepatic cholangiocarcinoma (ICC) is a malignant tumor originating from the secondary bile duct and its branch epithelium. Among primary liver tumors, the incidence of ICC is second only to hepatocellular carcinoma. Tumor microenvironment can regulate the occurrence and development of tumors. This study is dedicated to finding more markers that can diagnose ICC by finding the differential tumor microenvironment cells between ICC and normal tissues. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…CCA tumor tissues have high populations of activated DCs compared with normal tissues, indicating the association of DCs with liver cancer. 57 Although DCs are heterogeneous with various subsets, most DC phenotypes include myeloid DCs and plasmacytoid DCs. T cells are activated within lymph nodes, and mature myeloid DCs are decreased and plasmacytoid DCs are significantly increased in hepatic lymph nodes of HCC patients, suggesting functional differences depending on DC subsets in liver cancer.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…CCA tumor tissues have high populations of activated DCs compared with normal tissues, indicating the association of DCs with liver cancer. 57 Although DCs are heterogeneous with various subsets, most DC phenotypes include myeloid DCs and plasmacytoid DCs. T cells are activated within lymph nodes, and mature myeloid DCs are decreased and plasmacytoid DCs are significantly increased in hepatic lymph nodes of HCC patients, suggesting functional differences depending on DC subsets in liver cancer.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…The downregulated expression of TCR light chain reduced the reactivity of T cells to antigens or mitogens, resulting in the reduction of tumor specific immune response, so as to decrease tumor clearance and promote tumor progression [ 25 ]. Therefore, Arg-1 may affect the prognosis of ICC patients through the regulation of tumor immune microenvironment, which plays an important role in the development of ICC [ 26 , 27 ]. Other studies have shown that l -ornithine produced by Arg-1 could be further metabolized into polyamines, which were important components in cell differentiation and proliferation as well as promoting tumor growth [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…TAM-mediated inflammatory responses take on a critical significance in tumor transformation and progression, and they have been widely studied 90 . A bioinformatics analysis based on the gene expression omnibus database suggested that activated dendritic cells, M2 macrophages and regulatory T cells (Tregs) were expressed at higher levels in ICC than normal tissues, while M1 macrophages, monocytes, and helper T cells were expressed at lower levels in ICC than in normal tissues 91 . Thus, M2-TAMs has been the most studied macrophage cell type in the CCA tumor microenvironment.…”
Section: Advances Of Immune Cells In Ccamentioning
confidence: 99%